DIGITALIZATION AS A MODERATOR IN MSME MANAGEMENT, PLANNING, AND FINANCIAL PERFORMANCE - Rian Rahmat Ramadhan; Almuluk Fajar Zuhri (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the influence of management performance and financial planning on the financial performance of MSMEs, with digitalization as a moderating variable. The research was conducted on MSMEs in the food and beverage sector in Pekanbaru City using a quantitative approach. Data were collected through a structured questionnaire distributed to 100 business owners and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results show that management performance and financial planning have a significant positive effect on financial performance. Digitalization also has a significant direct effect on financial performance. However, it does not significantly moderate the relationship between management performance or financial planning and financial performance. These findings suggest that digitalization, while beneficial, is not yet fully leveraged by MSMEs as a strategic moderator. This study contributes to both theory and practice by offering new insights into the role of digital transformation in improving MSME performance.